Parametric study of a dual-band quasi-Yagi antenna for LTE application - Md Ashraful Haque; Mohd Azman Zakariya; Narinderjit Singh Sawaran Singh; Md. Afzalur Rahman; Liton Chandra Paul (Institute of Advanced Engineering and Science, 2023)
Due to small size and lightweight properties, the development of microstrip (MS) patch antennas for wireless communication has become one of the mobile application devices in demand in recent years. This has helped to reduce reliance on wired cables. In this paper, a study has been performed on MS antenna by developing a quasi-Yagi structure on a fire retardant-4 (FR-4) substrate with a MS to coplanar strip line (CPS) transition feeding technique. The antenna is designed by using computer simulation technology (CST) to achieve the desired resonant frequency and bandwidth. The proposed dual band quasi-Yagi antenna has impedance bandwidths of approximately 0.3 GHz and 0.22 GHz resonating at 1.80 GHz and 2.60 GHz, respectively, which makes it suitable for long-term evolution (LTE) applications. Eight-director elements in four pairs are constructed to achieve directivity with magnitudes of 6 dB and 8.3 dBi at both resonant frequencies, 1.80 GHz and 2.60 GHz, respectively. Different parametric studies have also been performed to characterize the antenna radiation characteristics. The return loss, voltage standing wave ratio (VSWR), front to back (F/B) ratio and far-field radiation are analyzed and discussed.